Effect of Solanum nudum steroids on uninfected and Plasmodium falciparum-infected erythrocytes (2009)
ABSTRACT: Steroids from Solanum nudum (SNs) have demonstrated antiplasmodial activity against erythrocytic stages of the Plasmodium falciparum strain FCB-2. It is well known that steroids can alter the membrane function of erythrocytes. Thus, we assessed alterations in the membranes of uninfected red blood cells, the parasite invasiveness and the solute-induced lysis of parasitised red blood cells (pRBCs). induced by SNs. We found that most merozoites were unable to invade SN-treated erythrocytes. However, transmission electron microscopy revealed no effect on the morphology of uninfected erythrocytes treated with either SN2 or diosgenone and neither SN induced haemolysis of uninfected erythrocytes. SN2 and SN4 inhibited isosmotic sorbitol and alanine-induced haemolysis of pRBCs. In contrast, diosgenone and SN1 did not inhibit solute-induced haemolysis. The inhibition of solute-induced lysis of parasitised erythrocytes by SN2 and SN4 suggest an action of these SNs on new permeability pathways of pRBCs.